2012
DOI: 10.1089/neu.2011.2141
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic Acid Pretreatment Confers Protection and Functional Improvements after Acute Spinal Cord Injury in Adult Rats

Abstract: Currently, few interventions have been shown to successfully limit the progression of secondary damage events associated with the acute phase of spinal cord injury (SCI). Docosahexaenoic acid (DHA, C22:6 n-3) is neuroprotective when administered following SCI, but its potential as a pretreatment modality has not been addressed. This study used a novel DHA pretreatment experimental paradigm that targets acute cellular and molecular events during the first week after SCI in rats. We found that DHA pretreatment r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
57
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 81 publications
10
57
0
1
Order By: Relevance
“…We recently reported that acute parenteral administration of DHA before injury leads to early improvements in conduction and locomotor function after SCI. 22 This finding is consistent with studies showing the efficacy of x-3 PUFAs as a post-treatment modality to ameliorate secondary damage and dysfunction. 12,[17][18][19][20][21][22][23][24] There is still a significant gap in our knowledge, however, concerning the therapeutic effects of prophylactic x-3 PUFAs against neurotrama.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…We recently reported that acute parenteral administration of DHA before injury leads to early improvements in conduction and locomotor function after SCI. 22 This finding is consistent with studies showing the efficacy of x-3 PUFAs as a post-treatment modality to ameliorate secondary damage and dysfunction. 12,[17][18][19][20][21][22][23][24] There is still a significant gap in our knowledge, however, concerning the therapeutic effects of prophylactic x-3 PUFAs against neurotrama.…”
Section: Introductionsupporting
confidence: 89%
“…[12][13][14][15][16] In contrast, x-3 PUFAs, such as DHA, are anti-inflammatory, confer neuroprotection, and play significant roles in facilitating functional recovery in various SCI animal models. 12,[17][18][19][20][21][22] One important hypothesis arising from our work and from other published epidemiological evidence is that dietary x-3 PUFAs can confer resiliency and facilitate recovery, even when administered before SCI. We recently reported that acute parenteral administration of DHA before injury leads to early improvements in conduction and locomotor function after SCI.…”
Section: Introductionmentioning
confidence: 65%
“…[20][21][22] As previously reported, essential n-3 PUFAs, especially DHA, have beneficial actions in many inflammatory diseases. [23][24][25][26] For example, in inflamed tissues at peripheral sites, DHA is released from immune cells such as neutrophils during the acute phase of the inflammatory process. 27) Most important thing in this study is that LPS stimulation specifically facilitated the release of DHA and ARA from astrocytes although SFAs did not change.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory activity of DHA could also derive from its direct effect on invading macrophages or microglia. Both in vitro and in vivo data highlight that DHA blocks invading macrophages and microglia activation and the signalling pathway (NF-kB) in the brain and spinal cord of several inflammatory rodents models (De Smedt-Peyrusse et al, 2008;Figueroa et al, 2012;Lim et al, 2013;Lu et al, 2013). Recent data highlight that in vitro DHA has not only anti-inflammatory activity but also promotes microglia to a M2 phenotype with increased Aβ42 phagocytosis (Hjorth et al, 2013).…”
Section: How Do N-3 Pufa Mechanisms Control Neuroinflammation?mentioning
confidence: 99%